(untitled) (Geography and Tourism, 2018)
The paper considers the main regularities indicating the activation of channel deformations in small and medium-sized rivers as a result of changes in slope and river runoff depending on the impact of degradation of landscape-na-ture complexes on catchment areas in the Southern Urals and the Cis-Urals as a result of human economic activity. The paper shows that changes in slope and river runoff contribute to the formation of the maximum water flow rate and the destructive force of water flows at the level of overlapping anthropogenic factors and natural historical processes. In accordance with the above, long-term changes in small and medium-sized river channels may occur in a multidirectional way. For example, it has been established that significant changes occurred in the conditions of increasing climate aridity and the growing human impact on landscape-nature complexes in the basins of small rivers in the period from the 1940s–1950s to the 1980s–1990s. They consist i.a. in the transformation of some small rivers of the 1st order into intermittent streams, or changes in the pattern of the hydrographic network.